3
$\begingroup$

First I will state the problem.

A chicken lays $n$ eggs. Each egg independently does or doesn’t hatch, with probability $p$ of hatching. For each egg that hatches, the chick does or doesn’t survive (independently of the other eggs), with probability $s$ of survival. Let $N\sim \text{Bin}(n,p)$ be the number of eggs which hatch, $X$ be the number of chicks which survive, and $Y$ be the number of chicks which hatch but don’t survive (so $X+Y =N$). Find the marginal PMF of $X$.

Intuitively, the probability that a egg hatches and chick survives is $ps$. We can consider each egg as a Bernoulli trial each with a success (hatching and surviving) probability $ps$. There are $n$ independent trials, so $X\sim \text{Bin}(n,ps)$.

But I am trying to prove this more rigorously.

For any $1\le i\le n$ we have $$P(X=i)=\sum_{j=0}^nP(X=i|N=j)P(N=j)\\=\sum_{j=i}^nP(X=i|N=j)P(N=j)\\=\sum_{j=i}^n\binom{j}{i}s^i (1-s)^{j-i}\binom{n}{j}p^j(1-p)^{n-j}$$

How do I show that the above sum collapses to $\binom{n}{i}(ps)^i(1-ps)^{n-i}$?

$\endgroup$
3
$\begingroup$

Your intuition is correct. Algebraic demonstration of that fact can proceed as follows:

$$\begin{equation} \begin{aligned} \mathbb{P}(X = i) &= \sum_{j=i}^n {j \choose i} s^i (1-s)^{j-i} {n \choose j} p^j (1-p)^{n-j} \\[8pt] &= \sum_{j=i}^n \frac{j!}{i! (j-i)!} \frac{n!}{j! (n-j)!} s^i (1-s)^{j-i} p^j (1-p)^{n-j} \\[8pt] &= \sum_{j=i}^n \frac{n!}{i! (j-i)! (n-j)!} s^i (1-s)^{j-i} p^j (1-p)^{n-j} \\[8pt] &= \sum_{r=0}^{n-i} \frac{n!}{i! r! (n-i-r)!} s^i (1-s)^r p^{r+i} (1-p)^{n-i-r} \\[8pt] &= \frac{n!}{i! (n-i)!} (ps)^i (1-p)^{n-i} \sum_{r=0}^{n-i} \frac{(n-i)!}{r! (n-i-r)!} (1-s)^r p^r (1-p)^{-r} \\[8pt] &= {n \choose i} (ps)^i (1-p)^{n-i} \sum_{r=0}^{n-i} {n-i \choose r} \bigg( \frac{(1-s) p}{1-p} \bigg)^r \\[8pt] &= {n \choose i} (ps)^i (1-p)^{n-i} \bigg( 1 + \frac{(1-s) p}{1-p} \bigg)^{n-i} \\[8pt] &= {n \choose i} (ps)^i (1-p)^{n-i} \bigg( \frac{1-p + p-ps}{1-p} \bigg)^{n-i} \\[8pt] &= {n \choose i} (ps)^i (1-p)^{n-i} \bigg( \frac{1-ps}{1-p} \bigg)^{n-i} \\[8pt] &= {n \choose i} (ps)^i (1-ps)^{n-i} \\[8pt] &= \text{Bin}(i | n, ps). \\[8pt] \end{aligned} \end{equation}$$

(Note that the seventh step, removing the summation, is an application of the binomial theorem.)

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.